Comparison of solar distillers for the obtaining of fresh water in wells of brackish water in the Peasant Community San Juan Bautista of Catacaos – Piura - Chiroque Luján, Roberto (2019)
Existing the need to obtain fresh water for human consumption for the benefit oflivestock associations located within the boundaries of the Sechura desert and the SanJuan Bautista de Catacaos Peasant Community, in Piura, an experimental scientific studywas carried out with the main objective compare different models of solar distillers,for at least 3 months, using brackish water from the artisanal well of farmers in theTabanco sector. (with a 95% confidence interval) In order to determine the design ofthe best suitable freshwater solar distiller, from the point of view, environmental andeconomic, the research applied the Bifactorial statistical model of Random Blocks anddid the analysis of variance that was complemented with the Tukey test; obtainingas a result that the solar distiller of two slopes is the most suitable design for theenvironmental conditions of the northern desert allowing a production of 1,509 to1,767 liters of water per day/m2 of water mirror, for the evaluation period of themonths of November to December, it is also the most economical, with a lower costof 34.1 soles over a 10-year horizon to have 20 liters of distilled water per day